Antimicrobial activity of a Polyherbal formulation containing Ocimum sanctum, Rubia cordifolia and Glycyrrhiza glabra extracts against different microbial species (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
In the present investigation, antimicrobial evaluation of individual creams of Ocimum sanctum, Rubia cordifolia, Glycyrrhiza glabra and their optimized polyherbal cream was carried out using commonly used gram positive bacteria (Staphylococcus aureus and Bacillus subtilis) gram negetive bacteria (Escherichia coli and Pseudomonas aeruginosa and fungi (Candida albicans and Aspergillus niger). The study reported that, both individual extract creams and polyherbal creams have shown antimicrobial activity. The Ocimum sanctum extract based cream was more effective against gram positive bacteria having more zone of inhibition (20±0.57, 15±0.05) than rest 04 species while Glycyrrhiza glabra extract based cream was more effective against gram negative bacteria having more zone of inhibition (20±1.0, 11±0.46) and fungi (10±0.46, 13±0.15). The Rubia cordifolia extract based cream reported to be less stronger action against all species as compared to above mentioned both the creams. Howevere, all the three creams were less potent than reference standard cream. The optimized polyherbal formulation showed enhanced zone of inhibition significantly, compared to individual extract based creams. The effect was even more than the reference standard cream against gram positive (22±0.28, 18±0.20) and gram negative (19±0.15, 22±0.35) bacteria, suggesting synergistic combination of ingredients. Thus study validated the usefulness of polyherbal cream consisting of Ocimum sanctum, Glycyrrhiza glabra and Rubia cordifolia against most common pathogens in dermatology, suggesting possible role to treat multidrug resistant mixed infections. This action may be attributed to synergistic actions of various phytoconstituents involved.